Реализация образовательной программы по подготовке специалистов для экологической модернизации энергетики в Причерноморье - Багрова, Л.А.; Бержанский, В.Н.; Беседина, Е.; Боков, В.А.; Мазинов, А.С.–А. (Культура народов Причерноморья, 2013)
Рассматриваются задачи международного проекта АРГОС по подготовке специалистов для экологической модернизации энергетики, описываются подходы к составлению совместимых учебных программ для ряда университетов Причерноморского региона, приводятся результаты по написанию студентами совместно с их коллегами из других стран магистерских и дипломных работ. Розглядаються завдання мiжнародного проєкта АРГОС по пiдготовцi специалiстів для екологичної модернiзацiї енергетики, додаються пiдходи до складання сумiсних навчальних програм для декiлькох унiверситетiв Причорноморського регiона, даються результати по пiдготовцi студентами разом з Їх колегами з iнших держав магiстерських та дипломних робiт. The article is devoted to the implementation of educational programs in the field of training of specialists with broad integrated approach to the analysis of relations of production, energy, society and the environment. The global trends of renewable energy sources development were analyzed. The core problem lies in the finding of the most effective teaching approaches to address greening energy. According to the article it can be solved within the framework of international programs for master student, young professionals and researchers from academia and industry. This article provides information about the course and the main stages of the international project BSUN Joint Master Degree Program on the Management of Renewable Energy Sources – ARGOS, which allows to unite experts from different countries (Romania, Moldova, Ukraine, Turkey, Bulgaria) to conduct research in the field of ecological energy modernization. Also, it is said about main results of the project – Master's thesis of Turida National Vernadsky University sudents in cooperation with their foreign colleagues. It is mentioned that a particular attention was paid to the course content harmonization, sharing the methodological recommendations, information, establishing common approaches to the scientific instruments understanding held by the mutual meetings, by organizing the presentations and videoconferences between the countries participating in the project (with the participation of both teachers and students). The article will be useful to researchers who are working towards greening management , modernization of energy, management of renewable energy sources.